Motivation of the Competence-based Evaluation through Rubrics and Assessment scales. Practical and Regulatory Aspects - García Rojas, Olivia Vanesa; Jiménez Alfaro, Jesús (Avances en Supervisión Educativa, 2025)
This article explores the significance of rubrics and rating scales as essential instruments for competency-based assessment within the educational system, in alignment with current educational legislation. It considers the advantages of these tools in promoting an objective, transparent, and continuous evaluation process, consistent with the competency-based model that supports the development of key competences in pupils. The discussion further addresses the right of students to a fair and impartial assessment, referencing relevant legal frameworks, including administrative regulations and rulings from both the Supreme Court and the Constitutional Court. The article underscores the importance of providing justification for grades, serving a dual purpose: to uphold students’ rights and to encourage their active engagement and academic progress. In addition, the article examines the challenges and practical difficulties associated with implementing such assessment tools, highlighting the pressing need for appropriate teacher training and the cultivation of an assessment culture geared towards ongoing improvement within the classroom.
Keywords: Student evaluation; educational qualifications; educational indicators; educational legislation; educational quality